Public’s Preferences for Community Pharmacy Attributes and Their Perceptions Towards Pharmacist-led Minor Ailment Services in Malaysia - Selvaraj, Amutha; Appalasamy, Jamuna Rani (Malaysian Journal of Medicine and Health Sciences, 2022)
Introduction: The prospect of public accessing community pharmacies for minor ailment advice or treatment highly depends on the pharmacy attributes and their staff. This study aimed to investigate the extent to which community pharmacies are used as a source of minor illness management and the public’s relative preferences for pharmacy features. Methods: A cross-sectional survey among the public in Malaysia was carried out between August and December 2020. The validated self-administered questionnaires were distributed at several pharmacies and shared via email, Whatsapp group, and Facebook. Results: A total of 141 from 153 public respondents completed the survey. From the descriptive and inferential analysis, it was found that about a third of the public goes to a pharmacy for advice or treatment for minor illnesses. The vast majority of respondents had positive perceptions that community pharmacists are knowledgeable and qualified to offer advice or treatment for minor diseases. A significant positive relationship was observed between pharmacy characteristics’ scores and pharmacy staff and pharmacy services’ scores (p<0.001). The increase in pharmacy staff score significantly increased the pharmacy services’ score (p<0.001). Conclusion: The implications of the public acknowledging specific attributes were crucial in further supporting community pharmacists’ services, especially in the private practice setting.